2006
DOI: 10.1063/1.2202754
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of electron-spin coherence in intrinsic bulk GaAs

Abstract: Temperature dependence of electron-spin coherence dynamics is investigated for an intrinsic bulk GaAs in the Voigt geometry using the elliptically polarized absorption quantum-beat spectroscopy. Temperature dependences of spin coherence and recombination lifetimes as well as g factor of electrons are reported over a temperature range from 8.1to260K. The temperature dependence of spin coherence lifetime (T2*) agrees well with a reported theoretical calculation and can be fitted well by a relationship T2*∼T−1∕2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
13
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
4
13
0
Order By: Relevance
“…An empirical relation for the energy ε dependence of the g factor in GaAs was found from experiments as g e (ε) = −0.44 + 6.3ε (ε in unit of eV) [225][226][227]. Experiments indicated that the g factor varies from −0.45 to −0.3 in the temperature range of 4-300 K [228][229][230][231][232]. Recent calculations [232] indicated that the temperature dependence of the g-factor is mainly due to the combined effects of (i) the energy-dependent g factor and (ii) the thermal dilatation of the lattice.…”
Section: Zeeman Interaction With External Magnetic Fieldmentioning
confidence: 98%
“…An empirical relation for the energy ε dependence of the g factor in GaAs was found from experiments as g e (ε) = −0.44 + 6.3ε (ε in unit of eV) [225][226][227]. Experiments indicated that the g factor varies from −0.45 to −0.3 in the temperature range of 4-300 K [228][229][230][231][232]. Recent calculations [232] indicated that the temperature dependence of the g-factor is mainly due to the combined effects of (i) the energy-dependent g factor and (ii) the thermal dilatation of the lattice.…”
Section: Zeeman Interaction With External Magnetic Fieldmentioning
confidence: 98%
“…The effect of spin-orbit coupling is strongly suppressed, arising from the spatial localization of electron and hole wave functions [5]. As a result, the spin relaxation time in low-dimensional structures is expected to be much longer than that of bulk counterpart even at room temperature [6][7][8][9]. At present, most studies of spin dynamics have been carried out in III-V or II-VI compound QDs at low temperature.…”
Section: Introductionmentioning
confidence: 97%
“…The magnetic field was applied parallel to the sample surface plane (Voigt configuration) by using a neodymium magnet. Magnitude of the applied magnetic field was 1.1 T. For control experiments, we have used undoped bulk GaAs samples because the electron g-factor for the undoped GaAs has been accurately examined at room temperature in some previous works [1,2,5]. The optical excitation energy for the optical measurements in bulk GaAs was 1.43 eV, which corresponds to band gap energy of GaAs at room temperature [2,16,17].…”
mentioning
confidence: 99%